2016
DOI: 10.1038/onc.2016.411
|View full text |Cite
|
Sign up to set email alerts
|

Cancer heterogeneity is not compatible with one unique cancer cell metabolic map

Abstract: The Warburg effect and its accompanying metabolic features (anaplerosis, cataplerosis) are presented in textbooks and reviews as a hallmark (general characteristic): the metabolic map of cancer. On the other hand, research articles on specific tumors since a few years emphasize various biological features of different cancers, different cells in a cancer and the dynamic heterogeneity of these cells. We have analysed the research literature of the subject and show the generality of a dynamic, evolving biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 77 publications
(111 reference statements)
3
67
0
1
Order By: Relevance
“…It is now clear that there is a not a single ‘metabolic map’ or ‘metabolic switch’ describing cancer cell metabolism [74], and the fate of glutamine varies with a range of parameters, including the tissue of origin of a cancer, the genetic aberrations which drive it, the tumor microenvironment, and possibly diet and host metabolism. The collective effect of these variables is striking, such that the metabolic phenotypes of cancer cells range from those that are highly dependent on catabolism of exogenous glutamine, to those that accumulate glutamine via de novo synthesis and are self-sufficient for glutamine requirements.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that there is a not a single ‘metabolic map’ or ‘metabolic switch’ describing cancer cell metabolism [74], and the fate of glutamine varies with a range of parameters, including the tissue of origin of a cancer, the genetic aberrations which drive it, the tumor microenvironment, and possibly diet and host metabolism. The collective effect of these variables is striking, such that the metabolic phenotypes of cancer cells range from those that are highly dependent on catabolism of exogenous glutamine, to those that accumulate glutamine via de novo synthesis and are self-sufficient for glutamine requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism is highly conserved to the specific taxa. 20 , 21 It was reported that cancer metabolome profiles are mainly associated with the malignancy. 22 Compared with NSLCC, SCLC is more malignant with shorter doubling time, higher growth fraction, and earlier development of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that individual cells in a population can be metabolically very different (Nikolic et al, 2013;van Heerden et al, 2014;Solopova et al, 2014;Kotte et al, 2015;Takhaveev & Heinemann, 2018). Metabolic heterogeneity has been found, for instance, not only in microbial cultures used for biotechnological processes (Xiao et al, 2016), but also in cells of human tumors (Strickaert et al, 2017). Because metabolic heterogeneity is connected with productivity and yield losses in biotechnological production processes (Xiao et al, 2016), and in cancer with limited therapeutic successes (Robertson-Tessi et al, 2015), it is key to identify metabolic subpopulations and to understand their emergence.…”
Section: Introductionmentioning
confidence: 99%